Achieving a successful e-government: Determinants of behavioral intention from Thai citizens’ perspective - Nookhao S. (2023)
From the COVID-19 pandemic, e-government is a crucial tool in managing crisis and coping with change through communication and collaboration between the government, private, and civil sectors. The objective of this study was to develop an e-government development success model from the perspective of Thai citizens using integrated multiple concepts and to examine factors affecting the behavioral intention of citizens in e-government. A sample is Thai people in all regions of Thailand (n = 540) and analyzes by Structural Equation Model (SEM). The hypothesis testing found that factors directly influencing behavioral intention were information quality, system quality, service quality, citizen satisfaction, perceived usefulness, computer self-efficacy, and trust in government. Trust in government was the most direct influencing factor and was the mediating variable between perceived privacy and perceived security leading to behavioral intention. The results will benefit governments in developing e-government to drive the digital economy and society further.